Bone Resorption in Ameloblastoma and Its Underlying Mechanism - Jackson, Jackson; Halim, Johni; Anggraeni, Rezky; Sandra, Ferry (Indonesian Journal of Cancer Chemoprevention, 2021)
Ameloblastoma, a tumor located in the jaw, grows slowly but locally invasive. Ameloblastoma expands in the jaw based on a mechanism resorbing the surrounding bone. To date, the bone resorption mechanisms of ameloblastoma are associated with the expression of receptor activator of nuclear factor (NF)-κB (RANK) ligand (RANKL), matrix metalloproteinases (MMPs), and tumor necrosis factor (TNF)-α. RANKL plays an important role in generating osteoclastogenesis. MMPs degrade the extracellular matrix. TNF-α can induce the formation of osteoclast and modulate the MMPs. In this review the bone resorption mechanism of ameloblastoma as well its signaling pathway will be disclosed.Keywords: Ameloblastoma, RANKL, MMPs, TNF-α.